Enabling the controlled assembly of antibody conjugates with a loading of two modules without antibody engineering - Lee, Maximillian T. W. (Royal Society of Chemistry, 2017)

(untitled) (Chem Sci)
The generation of antibody conjugates with a loading of two modules is desirable for a host of reasons. Whilst certain antibody engineering approaches have been useful in the preparation of such constructs, a reliable method based on a native antibody scaffold without the use of enzymes or harsh oxidative conditions has hitherto not been achieved. The use of native antibodies has several advantages in terms of cost, practicality, accessibility, time and overall efficiency. Herein we present a novel, reliable method of furnishing antibody conjugates with a loading of two modules starting from a native antibody scaffold.